1967
DOI: 10.1172/jci105686
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a Role of Physical Factors as Determinants of the Natriuretic Response to Volume Expansion*

Abstract: Abstract. The importance of plasma protein concentration, renal vascular resistance, and arterial pressure as mediators of the natriuretic response to volume expansion was investigated in anesthetized dogs.Saline loading depressed plasma protein concentration and increased arterial pressure but did not decrease renal vascular resistance. Restoring plasma protein concentration by infusing hyperoncotic albumin increased sodium reabsorption and decreased sodium excretion during saline loading despite simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
1
2

Year Published

1969
1969
1992
1992

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(77 citation statements)
references
References 15 publications
8
66
1
2
Order By: Relevance
“…With regard to this latter change, they suggested that the distensibility of the proximal tubule might be limited during rapid saline infusion because of an increase in hydrostatic pressure, or a fall in colloid oncotic pressure in the peritubular capillaries, and a resultant increase in interstitial volume proximal tubular volume to GFR/nephron. (26,28,29). The rise in GFR which often occurs in the rat during saline loading would thus not be accompanied by a proportionate increase in the volume of the proximal tubule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to this latter change, they suggested that the distensibility of the proximal tubule might be limited during rapid saline infusion because of an increase in hydrostatic pressure, or a fall in colloid oncotic pressure in the peritubular capillaries, and a resultant increase in interstitial volume proximal tubular volume to GFR/nephron. (26,28,29). The rise in GFR which often occurs in the rat during saline loading would thus not be accompanied by a proportionate increase in the volume of the proximal tubule.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism by which a rise in peritubular capillary pressure might inhibit proximal sodium transport is unknown. Earley, Martino, and Friedler (26,28,29) have postulated that increases in pressure within the capillaries delay the removal of the tubular reabsorbate, thus causing an increase in the interstitial volume of the kidney. Lewy and Windhager (10) and Nutbourne (33) suggested that an increase in renal interstitial volume might create a layer of high sodium concentration within the basal labyrinth adjacent to the transporting membrane of the tubular epithelium which might then interfere with the active sodium pump mechanism or enhance back-diffusion of sodium into the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic and physical factors can also influence salt excretion (25). Koehn, Schindler, and Stanton (26) demonstrataed that aortic perfusion pressure was reduced by approximately 17% in radiothyroidectomized rats; Reville and Stephan (7,19) found an elevated plasma protein concentration in dehydrated hypothyroid rats; and Osorio and Zadunaisky (20) demonstrated that the clearance of Diodrast was decreased by 66% in conjunction with a 33% reduction in the Ctn and resulted in an increased filtration fraction in these animals.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies that evaluated COP effects on urine excretion were performed before the discovery of many factors now known to influence sodium excretion and were therefore not well controlled. 27 " 29 Because changes of COP can substantially alter renal excretion, these relations need to be explored in salt-sensitive forms of hypertension.…”
Section: Control Of Sodium Excretionmentioning
confidence: 99%